CONTEMPORARY UKRAINIAN SINGING-POETIC CREATIVITY AND FOLKLORIC ELEMENTS OF SHEVCHENKO’S “KOBZAR” - Karbashevs’ka, O. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
Taras Shevchenko’s poetic heritage is examined in the context of Revolution of dignity and “Euromaidan” songs of the end of 2013 – the beginning of 2014. Processes of consolidating Shevchenko as a dominating symbol of Ukrainian mass culture of the first decades of the XXIst century are traced. The attention is focused on folkloric roots of Shevchenko’s word as one of the premises of permanent incorporation of the poet’s legacy into the life of Ukrainian community.